2021
DOI: 10.1111/aec.13037
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the threat of landscape transformation and habitat fragmentation in a global biodiversity hotspot

Abstract: Habitat loss and habitat fragmentation are amongst the major drivers of biodiversity loss globally. Although habitat fragmentation poses additional threats to biodiversity beyond habitat loss alone, the IUCN’s Red List of Ecosystems (RLE) does not provide guidance on how to assess these threats. This study develops an approach for incorporating habitat fragmentation into the RLE threat assessment and investigates additional insights such an analysis could provide beyond the analysis of distribution trends. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The high rate of habitat loss in these parks is considered the main driver of the loss of wildlife in SSA [19][20][21]. These land uses not only fragment the landscape, as indicated by the landscape analysis, but also destroy sensitive habitats and inhibit the natural movements of animals [97].…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of habitat loss in these parks is considered the main driver of the loss of wildlife in SSA [19][20][21]. These land uses not only fragment the landscape, as indicated by the landscape analysis, but also destroy sensitive habitats and inhibit the natural movements of animals [97].…”
Section: Discussionmentioning
confidence: 99%
“…Landscape or habitat fragmentation is the result of a gradual reduction in the natural environmental surface as well as its progressive isolation (Ziv and Davidowitz 2019). This process is one of the main threats to biodiversity (Hanski 2015;Fletcher et al 2018;Ntshanga et al 2021). This study showed that, on a small scale, the plant diversity level of a park is less affected by the landscape surrounding the park, i.e., roads, buildings and green space within the buffer zone have weaker correlations with species richness, and Margalet, Shannon and Simpson indices.…”
Section: Effects Of Exterior Characteristics On Species Diversitymentioning
confidence: 99%
“…Nonetheless, the natural biodiversity that underpins the persistence of fynbos wild edible species is currently threatened by conventional agriculture, urbanisation, encroachment by alien invasive species, and climate change (Midgley and Bond 2015;Richardson et al 2018;Ntshanga et al 2021). Furthermore, much of the traditional ecological knowledge (TEK) around the use of NUS in the Cape Floristic Region is considered either lost or declining (Philander 2010;de Vynck et al 2016a;Botha et al 2020).…”
Section: Data Collection and Analysismentioning
confidence: 99%